Qualidade fisiológica de sementes de Sebastiania commersoniana (Baill.) Smith & Downs (branquilho - Euphorbiaceae) durante o armazenamento - Dos Santos, Sérgio Roberto Garcia; De Paula, Rinaldo Cesar [UNESP] (My University, 2007)
This paper aims to evaluate the physiological quality of Sebastiania commersoniana seeds stored in cloth bag, plastic bag and glass container and kept in two conditions: laboratory workbench and cold chamber (4 ± 2°C e 80% relative humidity - RH) for 531 days. Periodically, samples were taken in order to determine the moisture content and to perform germination tests. The experimental design was completely randomized, in factorial scheme of 3 × 2 (wrappings × conditions), for each period of storage evaluated (0, 158, 271, 389 and 531 days of storage). Supplementary, a polynomial regression was adjusted in order to describe the physiological quality of the seeds for the different conditions during the experimental period. The results lead to the following considerations: a) storage under variable temperature and air humidity (laboratory workbench) can be used for periods of over five and a half months, with the seeds stored in cloth bag, plastic bag or glass container; b) the physiological quality of the seeds was not hardly altered when stored in cold chamber in cloth bag, plastic bag and glass container for over 18 months.
Physiological quality of Sebastiania commersoniana (Baill.) Smith & Downs seeds (branquilho - Euphorbiaceae) during storage
Keywords: Forest seeds; Seed conservation; Vigor; Glass container; Atmospheric humidity; Forestry; Physiology; Plastic products; Seed; Containers; Plastic Bags; Seeds